Exposure assessment and carcinogenic risk characterization of industrial chemical emissions in incheon, South Korea - Yeowool Choi; Hyewon Kim; Tae-Yong Jeong; Sang Don Kim (Scientific Reports)
Abstract Rapid industrialization has intensified chemical emissions, raising urgent concerns about carcinogenic risks to surrounding communities. This study assessed the spatial distribution of industrial facilities emitting chemicals in Incheon Metropolitan City, South Korea, with a particular focus on Group 1 carcinogens. Using Geographic Information System (GIS) and multimedia exposure model (SimpleBox), we estimated exposure levels and cancer risks for residents within a 1-km radius of industrial facilities. The results demonstrated that approximately 22% of the region’s population resides near chemical emission sources, with vulnerable facilities, including kindergartens, elementary schools, and medical institutions, located in these affected areas. Of particular concern, 9.4% of residents are potentially exposed to Group 1 carcinogens, including formaldehyde, benzene, chromium compounds, trichloroethylene, and cadmium compounds. Cancer risk assessments for chromium and cadmium compounds exceeded EPA management standards. This research underscores the urgent need for enhanced emission management policies at industrial facilities, the establishment of protective buffer zones, and strengthened collaboration between local communities and industries to mitigate these significant health risks.